ANALISIS IMPLEMENTASI VISUAL STORYTELLING MARKETING DAN BRAND TRUST SERTA PENGARUH TERHADAP MINAT BELI KOSMETIK WARDAH PADA MAHASISWA DI PURWAKARTA - Ade Nurhayati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Competition in the beauty market are very competitive, business actors in the cosmetic industry are required to carry out various effective marketing strategies so that buying interest in Wardah cosmetics increases. One of them is by utilizing promotions on social media platforms effectively. This study was conducted to determine what factors influence the interest in buying Wardah cosmetics among female students in Purwakarta. In this study, two independent variables were taken, namely visual storytelling marketing and brand trust and buying interest in Wardah cosmetics as the dependent variable. Primary data collection using cluster sampling technique by distributing questionnaires to 98 respondents, with a quantitative research model with descriptive verification method. The data analysis method used in this study is multiple linear regression with the help of IBM SPSS 22 software. Based on the results of research and tests that have been carried out, it shows that partially visual storytelling marketing and brand trust have a positive and significant effect on buying interest in Wardah products. And all independent variables have a simultaneous effect on buying interest with a value of Fcount 50.7 with a significance level of 0.000 <0.05. And the value of R Square shows the results of 0.581 which means that the entire dependent variable has a simultaneous effect of 58.1%